ASSESSMENT OF RECEPTOR CONVERSION ROLE FOR ADVANCED BREAST CANCER ON THE CHEMORESISTANCE OCCURRENCE - Oleksii V. Movchan; Ivan I. Smolanka; Andriy O. Lyashenko; Anton D. Loboda; Iryna V. Dosenko; Oksana M. Ivankova (Клінічна та профілактична медицина)
Introduction. Neoadjuvant chemotherapy (NC) is employed as an important step in the treatment of patients with breast cancer (BC). We do not have much information about the conversion of estrogen receptor (ER) and/or progesterone receptor (PR) status in breast cancer (BC) patients after NC, or about its correlation with chemoresistance and prognosis. Not all clinics consistently determine receptor status after neoadjuvant chemotherapy (NC) and surgical intervention in breast cancer (BC) patients. However, this status may vary, making it critical to adjust the adjuvant treatment plan accordingly. Failure to do so may result in inadequate therapy and the development of chemoresistance.